Isabel Bertolucci Cerruti: trajetória de uma militante política em São Paulo (1910-1937) - Almeida, Daniela Fernanda De [UNIFESP] (2019)
This research aimed to reconstruct the political life and intellectual trajectory of an important libertarian activist: Isabel Bertolucci Cerruti. More particularly, it presents and discusses its social and political ideas spread in the first decades of the last century of 1910, 1920 and 1930, a period of active militancy in associations, workers 'and antifascists' journals. Although Isabel Cerruti lived until the 1970s, the option for a narrower chronological cut sought to apprehend the militant's relationship with the organized universe of newspapers, political groups linked to the working class and their manifestations, such as strikes, campaigns, and their sociability politics in general between the period of beginning of militancy (decade 1910) and the phase of adherence to Italian antifascism in São Paulo (1920s and 1930s), through the intense strike period of 1917-19. In addition to specialized bibliography, the study is based on research in primary sources, such as the medical records organized by the political police (DEOPS), the articles signed by Cerruti in the periodicals published in São Paulo A Plebe, A Obra, A Lanterna and La Difesa. Therefore, the objectives of the present work are: to investigate the political life of Isabel Cerruti (general objective); to study her professional trajectory, to understand her positions and approaches between different political projects throughout her life, to understand what it means to be a militant woman. We still want to analyze their circles of sociability with elements of Italian ethnicity and understand their female contribution to the working class between the First Republic and the installation of the Vargas dictatorship.